The role of E-administration in achieving information security in governmental organizations (Field Study on the Employees of Ministry of Commerce - Makkah al-Mukarramah Region) 2019-2022 - Alqahtani, Sharifah Abdulmosen; Alshamasi, Areej Abdulrahman (Journal of Economic, Administrative and Legal Sciences, 2022)
This study aimed to know the role of electronic management in its dimensions (electronic devices, electronic software, electronic systems) in achieving information security in the Ministry of Commerce in the Western Region.) from a research population of (350) employees and it is employees of the Ministry of Commerce, where the data was processed using the statistical packages program (SPSS). Where the study reached a number of results, the most important of which are: There is a statistically significant effect between each dimension of electronic management and information security according to the point of view of employees at the Ministry of Commerce, and the largest effect of the dimension of electronic programs was with an arithmetic mean (3.75) of high relative importance, and there is a significant effect statistics on the level of information security in the Ministry of Commerce, where it came to a medium rate in general and an arithmetic average of (3, 65), and finally the study made several recommendations, including: Establishing an experimental environment using digital technologies so that it is subject to control and management of the situation before applying any new electronic system, working on Achieving the strategic goal of the Ministry of Commerce, which stipulates “enabling the highest levels of digital maturity and readiness.” The department must also be rehabilitated by providing it with all material and technical electronic needs while providing anti-viruses and updating them periodically, focusing on network weaknesses and monitoring them, and benefiting from the National Information Security Program. "آمن".